PENGARUH PENGGUNAAN PUPUK NPK PELANGI DAN PUPUK HUMEGA CRUMBLERS TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis gueneensis Jacq ) - Gusti Nyoman Semarabawa, Abdul Fatah (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2012)
Objective of the research was to study the effect of NPK Pelangi and Humega Crumblers fertilizers, as well as their interaction on the growth of oil palm seedling.  The research was carried out in Sabintulung Village, Muarakaman Sub Disctrict of Kutai Kartanegara, East Kalimantan Province.  It took about 4 months from January to April 2012.  The Completely Randomised Design was employed for this research with factorial 4 x 4 and 3 replications.  The first factor was NPK Pelangi fertilizer application (p), consisted of 4 sub factors: No NPK Pelangi fertilizer application (p0), 30 g NPK Pelangi (p1), 60 g NPK Pelangi (p2), 90 g NPK Pelangi (p3).  And the second factor was application of Humega Crumblers fertilizer (h), consisted of 4 factors : No Humega Crumblers (h0), 20 g Humega Crumblers (h1), 40 g Humega Crumblers (h2), and 60 g Humega Crumblers (h3).  Results of the research revealed that the application of NPK Pelangi affect significantly on the increment of stem diameter at 10 weeks old after planting,  increment of petiole number at 14 weeks old, and number of fully open leaves (pinnate) at 14 weeks old.  But it did not affect significantly on the increment of seedling height at 6 and 10 weeks old after planting, and increment of stem diameter at 6 and 14 weeks old, and increment of petiole number at 6 and 10 weeks old.  The application of Humega Crumbles gave significant effect on the increment of stem diameter at 10 weeks old after planting, and the increment of petiole number at 14 weeks old, but it did not affect significantly on the increment of seedling height at 6, 10 and 14 weeks old after planting, increment of stem diameter at 6 and 14 weeks old, the increment of petiole number at 6 and 10 weeks old, and number of fully open leaves at 14 weeks old.  Meanwhile, the interactions between NPK Pelangi and Humega Crumbles fertilizers did not affect significantly on all parameters observed.